Adults with cystic fibrosis have deficits in bone structure and strength at the distal tibia despite similar size and measuring standard and relative sites - Nishiyama, Kyle K.; Agarwal, Sanchita; Kepley, Anna; Rosete, Fernando; Hu, Yizhong; Guo, X. Edward; Keating, Claire L.; DiMango, Emily A.; Shane, Elizabeth (Bone (New York, N.Y.), 2018)
Individuals with cystic fibrosis (CF) have lower bone mineral density (BMD) by DXA and are at higher risk of fracture than healthy controls. However, the 2-dimensional measurement of areal BMD (aBMD) provided by DXA is influenced by bone size and the true extent of the bone deficit is unclear. Our objective was to use high-resolution peripheral quantitative computed tomography (HR-pQCT) and individual trabecula segmentation (ITS) analysis to compare volumetric BMD (vBMD), microarchitecture and estimated strength at the distal radius and tibia in 26 young adults with CF and 26 controls matched for age, gender, and race. To assess the effect of limb length and minimize the confounding effects of size on HR-pQCT outcomes, we scanned participants at both the standard fixed HR-pQCT measurement sites and at a subject-specific relative site that varied according to limb length. CF participants did not differ significantly in age, height, weight, or BMI from controls. Ulnar and tibial lengths were 9mm shorter in CF patients, though differences were not significant. CF patients had significantly lower BMI-adjusted aBMD by DXA at the lumbar spine (8.9%, p<0.01), total hip (11.5%, p<0.01) and femoral neck (14.5%, p<0.01), but not at the forearm. At the fixed radius site, thickness of trabecular plates and torsional stiffness were significantly lower in CF participants than controls. At the relative radius site, only torsional stiffness was significantly lower in CF participants. At the tibia, total, trabecular and cortical vBMD were significantly lower at both fixed and relative sites in CF participants, with fewer, more widely-spaced trabecular plates, lower trabecular connectivity, and lower axial and torsional stiffness. Our results confirm that aBMD is lower at the spine and hip in young adults with CF, independent of BMI and body size. We also conclude that vBMD and stiffness are lower at the weight-bearing tibia. The pathogenesis of these differences in bone density and strength at the tibia appear to be related to trabecular drop-out and reduced trabecular connectivity and to be independent of differences in limb length, as assessed by scanning participants at both standard and relative sites. We concluded that significant deficits in bone structure and strength persist in young adults with CF, despite advances in care that permit them to attain relatively normal height and weight. •We used HR-pQCT to examine both a fixed and relative site in participants with cystic fibrosis (CF) and matched controls•We found impaired bone at both the radius and tibia in CF participants compared to controls•Deficits in bone structure and strength persist in young adults with CF, despite advances in care